The Health Resources and Services Administration (HRSA) Ryan White HIV/AIDS Program's Response to the Opioid Epidemic. (2nd September 2020) - Chavis, Nicole S; Klein, Pamela W; Cohen, Stacy M; Dempsey, Antigone; Hauck, Heather; Cheever, Laura W
Abstract: Background: The United States is in the midst of an unprecedented opioid crisis with increasing injection drug use (IDU)-related human immunodeficiency virus (HIV) outbreaks, particularly in rural areas. The Health Resources and Services Administration (HRSA)'s Ryan White HIV/AIDS Program (RWHAP) is well positioned to integrate treatment for IDU-associated HIV infections with treatment for drug use disorders. These activities will be crucial for the "Ending the HIV Epidemic: A Plan for America" (EHE) initiative, in which 7 southern states were identified with rural HIV epidemics. Methods: The RWHAP Services Report data were used to assess the IDU population and substance use services utilization among RWHAP clients in 2017, nationally and in the 7 EHE-identified states. THe HRSA held a 1-day Technical Expert Panel (TEP) to explore how RWHAP can best respond to the growing opioid crisis. Results: During the TEP, 8 key themes emerged and 11 best practices were identified to address opioid use disorder (OUD) among people with HIV. In 2017, among RWHAP clients with reported age and transmission category, 6.7% (31 683) had HIV attributed to IDU; among IDU clients, 6.3% (1988) accessed substance use services. Conclusions: The TEP results and RWHAP data were used to develop implementation science projects that focus on addressing OUD and integrating behavioral health in primary care. These activities are critical to ending the HIV epidemic.